On the High Winds in the Tianshan Grand Canyon in Northwest China: General Features, Synoptic Conditions, and Mesoscale Structures - Xi, Tao; Xu, Xin; Wei, Peng; Wang, Yuan; Ming, Jie; Zhang, Shushi; Ding, Jinfeng; Abulikemu, Abuduwaili (Frontiers in Earth Science, 2022)
This work studies the characteristics of high winds in the Tianshan Grand Canyon (TGC), Northwest China by using surface wind observations at six automatic weather stations during 2017-2018. Three high wind indices are examined, namely, high wind hour (HWH), station high wind event (SHWE) and regional high wind event (RHWE). SHWE denotes persistent high winds of more than 3 hours at an individual station while RHWE is defined for the southern TGC as a whole. High winds are mainly northwesterly/westerly, occurring predominantly in southern TGC. HWHs most often occur in spring and summer, while winter and spring HWHs possess the strongest intensity. The occurrence of HWHs exhibits an apparent diurnal variation, most frequent in the afternoon and evening while least from mid-night to early morning. SHWEs and RHWEs are prone to take place in spring, possessing relatively long lifetime and strong intensity. According to composite analysis of the 0.25° FNL reanalysis, favorable synoptic conditions are obtained for the persistent high winds in spring. Of great importance is the mid-tropospheric trough in the mid-high latitudes located to the north (i.e., upstream) of the TGC. The cold advection behind the trough cools and stabilizes the mid-lower troposphere, while the post-trough sinking motion causes a surface high that accelerates the low-level northwesterly wind. The synoptic thermal and dynamical forcing help set an upstream flow of moderate Froude number such that the mesoscale orographic flow traversing the TGC is in the nonlinear high-drag regime. Large-amplitude gravity waves are excited, with the isentropes descending abruptly over the lee slope which resembles internal hydraulic jump. Downslope windstorms are produced at the expense of flow potential energy as the subcritical upstream flow is transitioned to supercritical at the TGC peak. These findings have important implications on the formation and prediction of high winds in the TGC.